Sense of being stared at and other unexplained powers of human minds - Sheldrake, Rupert (Rochester, Vermont Park Street Press, 2003)
Drawing on more than 5,000 case histories, 4,000 questionnaire responses, and the results of experiments on staring, thought transference, phone telepathy, and other phenomena carried out with more than 20,000 people as well as reports and data from dozens of independent research teams, Sheldrake shows that these unexplained human abilities--such as the sense of being stared at--are not paranormal but normal, part of our biological nature. He reveals that telepathy depends on social bonds and traces its evolution from the connections between members of animal groups such as flocks, schools, and packs. Sheldrake shows that our minds and intentions extend beyond our brains into our surroundings with invisible connections that link us to each other, to the world around us, and even to the future.
Preface -- Introduction: unexplained abilities and extended minds -- The power of attention -- The sense of being stared at -- Surveillance -- Animal sensitivity -- Experiments on the power of looks -- The evil eye -- Are images in the brain? -- Telepathy -- Picking up thoughts and intentions -- Experiments on thought transference -- Telepathic calls -- Distant deaths and distress -- The effects of intentions at a distance -- Telephone telepathy -- The evolution of telepathy -- Remote viewing and feeling the future -- Remote viewing -- Animal premonitions -- Human forebodings -- Exploring precognition -- How do extended minds work? -- Extended minds and mental fields -- Notes -- Bibliography -- Index of names -- Index of subjects.
100545
Keywords: Telepathy; Precognition; Attitude (Psychology)